A Study on Performance Characteristics of Motorbike Engine Using Biogas from the waste of pig farm - Vũ Thị Kim Châu,; Chiêm Trấn Lâm,; Huỳnh Thanh Công, (Journal of Technical Education Science, 2012)
To determine the characteristics of the motorcycle engine using biogas as a basis for practical applications, the intake system of 110cm3 motorbike engine was modified to use biogas fuel. High CO2 in the biogas composition can slow the fire and cause instability in the fire. In this study, CO2 accounts for about 25% of input, the motor is installed with 75% load operation to ensure smooth operation and reliability. Engine speed in the test varied from 1500 rpm (no load speeds) up to 3500 rpm for each step is 500 rpm. Results obtained from experimental biogas is compared with results obtained from testing gasoline. In the same test conditions, the test showed that the biogas is a mixture of air-fuel denser than when tested with gasoline, so fuel consumption rates using higher biogas. Break thermal efficiency of biogas was found to be lower than gasoline about 3% of the total gas rate range tested. Components of the engine exhaust using biogas CO, HC are in the range allowed by the emission standards of Vietnam (CO <4,5% HC <1200ppm).